Evaluation of a 12-mm diameter covered self-expandable end bare metal stent for malignant biliary obstruction - Nakaoka, Kazunori; Hashimoto, Senju; Kawabe, Naoto; Nakano, Takuji; Kan, Toshiki; Ohki, Masashi; Ochi, Yuka; Takamura, Tomoki; Kurashita, Takamitsu; Nomura, Sayuri; Koyama, Keishi; Fukui, Aiko; Yoshioka, Kentaro (Endoscopy International Open, 2018)
Background and study aims Biliary metallic stents are used to drain unresectable malignant distal biliary obstructions. This study aimed to evaluate the efficacy of a novel 12-mm-diameter covered, self-expandable end bare metal stent (12-mm CSEEMS).Patients and methods We evaluated 99 patients with unresectable malignant distal biliary obstructions treated with covered biliary metallic stents. Of the 99 patients, 33 underwent 12-mm CSEEMS placement between June 2015 and April 2017 (12-mm-CSEEMS group) and 66 underwent 10-mm fully-covered self-expandable metal stent (FCSEMS) placement between January 2010 and July 2015 (10-mm-FCSEMS group). The overall survival (OS), the recurrent biliary obstruction (RBO), cause of RBO, time to RBO (TRBO) and adverse events in 12-mm-CSEEMS group and 10-mm-FCSEMS group were evaluated retrospectively.Results The OS tended to be longer in the 12-mm-CSEEMS group (log rank, P = 0.081) and TRBO was significantly longer in the 12-mm-CSEEMS group (log rank, P = 0.001) than in the 10-mm-FCSEMS group. Both univariate (HR, 0.449; 95 % CI, 0.27967 – 0.72215; P = 0.001) and multivariate (HR, 0.458; 95 % CI, 0.28395 – 0.73744; P = 0.001) Cox hazard analysis found that risk of RBO was significantly lower in 12-mm CSEEMS than in 10-mm FCSEMS. There were no significant differences between the 12-mm-CSEEMS group and 10-mm-FCSEMS group regarding the cause of RBO and adverse events.Conclusions The 12-mm CSEEMS showed a low risk of RBO compared with 10-mm FCSEMS and was considered to be effective and safe for draining unresectable malignant distal biliary obstruction.